HZSM-5 zeolites containing impurity iron species for the photocatalytic reduction of CO2 with H2O. Issue 20 (15th September 2016) - Tong, Yuecong; Zhang, Yingguang; Tong, Na; Zhang, Zizhong; Wang, Ying; Zhang, Xiaoyan; Zhu, Shuying; Li, Fuying; Wang, Xuxu
Abstract : The impurity [Fe 3+ –O 2− ] species in HZSM-5 zeolite is predominantly tetrahedrally coordinated and is the photoactive centre for photocatalytic CO2 conversion. Abstract : We report the application of the commercial HZSM-5 zeolite as an efficient and stable photocatalyst for the photoreduction of CO2 with H2 O at room temperature. CO and H2 were the main reduction products besides a trace amount of hydrocarbons. The activity of CO evolution was dependent on the source of various zeolites. The highest CO evolution rate over the HZSM-5 samples was 3.32 μmol g −1 h −1 under UV-light irradiation. The control experiments combined with the characterization results of XRD, UV-vis DRS and ESR revealed that the photocatalytic activity was not related to Si/Al ratios or Al–O units but was associated with the content of Fe impurities in the zeolite samples. A reaction mechanism of CO2 photoreduction on Fe species in zeolites was proposed. [Fe 3+ –O 2− ] species as a photoactive centre can be excited by UV light to form a charge-transfer excited state, [Fe 2+ –O − ]*, which was responsible for the CO2 reduction reaction. This work demonstrates zeolite molecular sieves as an efficient photocatalyst for CO2 conversion and helps us to understand the photocatalytic nature of zeolites.